Investigating the viability of sulfur polymers for the fabrication of photoactive, antimicrobial, water repellent coatings. Issue 22 (19th April 2022) - Upton, Rebekah L.; Dop, Romy A.; Sadler, Emma; Lunt, Amy M.; Neill, Daniel R.; Hasell, Tom; Crick, Colin R.
Abstract : A novel superhydrophobic coating prepared from an inverse vulcanized copolymer and SiO2 nanoparticle composite, exhibiting antibacterial properties, photocatalytic behaviour and UV stability. Abstract : Elemental sulfur ( S 8 ), a by-product of the petroleum refining industries, possesses many favourable properties including photocatalytic activity and antibacterial activity, in addition to being intrinsically hydrophobic. Despite this, there is a relative lack of research employing elemental sulfur and/or sulfur copolymers within superhydrophobic materials design. In this work, we present the use of sulfur copolymers to produce superhydrophobic materials with advanced functionalities. Using inverse vulcanization and the use of a natural organic crosslinker, perillyl alcohol (PER), stable S8 -PER copolymers were synthesised and later combined with silica (SiO2 ) nanoparticles, to achieve highly water repellent composites that displayed both antimicrobial and photocatalytic properties, in the absence of carcinogenic and/or expensive materials. Here, we investigated the antibacterial performance of coatings against the Staphylococcus aureus bacterial strain, where coatings displayed great promise for use in antifouling applications, as they were found to limit surface adhesion by more than 99%, when compared to uncoated glass samples. Furthermore, UV dye degradation tests were performed, utilizing the commercially available dye resazurin, and it was shown that coatings had the potential to simultaneously exhibit surface hydrophobicity and photoactivity, demonstrating a great advancement in the field of superhydrophobic materials.